Therapeutic monitoring of vancomycin = Monitorização terapêutica da vancomicina - Sergio Seiji Yamada; Gessilda Alcantara Nogueira de Melo; Maria Luiza Pereira Alves; Paula Nishiyama (Universidade Estadual de Maringá, 2012)
The present study aimed to characterize admitted patients in a public hospital in the Northwestern region of Paraná State, which were subject to therapeutic monitoring of vancomycin during 2007 and 2008. The data were obtained by a retrospective study of patients' medical records, from where we separated the laboratory results, medical prescriptions, gender, age, and diagnosis of patients submitted to therapeutic monitoring. Of the total of 38 patients, only eight (21.1%) presented serum concentrations within recommended range, varying from 1.3 to 47.9 mg L-1. Concentrations above the reference value were observed in 22 patients (57.9%), and below the reference, in other eight patients (21.1%). The recommended serum concentrations at peak were obtained in only four patients (11.4%), higher than the recommended value in seven patients (20.0%), and lower, in 24 patients (68.6%). Only one patient (2.6%) presented serum concentration within the reference values at both high and low dosages. Therefore, the results evidenced the importance of therapeutic monitoring of vancomycin, individualizing the dose for each patient, and reducing toxic or subtherapeutic effects of this antimicrobial substance. O objetivo deste trabalho foi realizar a caracterização dos pacientes internados em um hospital público da região Noroeste do Estado do Paraná que foram submetidos à monitorização terapêutica da vancomicina no período de 2007 a 2008. Os dados foram obtidos por meio de um estudo retrospectivo dos prontuários dos pacientes. Foram separados para este estudo os resultados laboratoriais, prescrições médicas, gênero, idade e diagnóstico dos pacientes que foram submetidos à monitorização terapêutica de vancomicina. Do total de 38 pacientes, em apenas oito (21,1%) as concentrações séricas no vale se encontravam na faixa recomendada variando de 1,3 a 47,9 mg L-1. Foram observadas concentrações acima do valor de referência em 22 pacientes (57,9%) e concentrações abaixo do valor de referência em outros oito pacientes (21,1%). As concentrações séricas recomendadas no pico foram obtidas em apenas quatro pacientes (11,4%), acima do valor de referência em sete pacientes (20,0%) e abaixo em 24 pacientes (68,6%). Apenas um paciente (2,6%) apresentou o nível sérico de vancomicina dentro do valor de referência em ambas as dosagens de pico e vale. Diante desses dados, confirmamos a necessidade da realização da monitorização terapêutica da vancomicina, individualizando a dose minimizando os efeitos tóxicos ou subterapêuticos do antimicrobiano.